Synthesis and antioxidant evaluation of novel sophisticated carboxamides based on 3-(ethoxycarbonyl)-4,5,6,7-tetrahydro-1-benzothiophen-2-amine - Gouda, Moustafa Ahmed; El Bialy, Serry Atta Atta (European Journal of Chemistry, 2014)
Condensation of cyanoacetamide 3 with cycloalkanones and elemental sulfur in the presence of morpholine yielded the bisthiophenes 4 and 5. Also, its (3) condensation with terphthalaldehyde or coupling with p-phenylenedidiazonium chloride afforded compound 13 and 14, respectively. Furthermore, cyanoacetylation of compound 4 or 5 afforded the cyanoacetamides 6 and 7, respectively. Knoevenagel condensation of compound 7 with aromatic aldehyde afforded the arylidenes 10, 11 and coumarin 12, respectively. Treatment of compound 3 with CS2 in DMF/KOH followed by alkylation reaction with ethyl bromoacetate afforded the triester derivative 16, which gave 3-aminothiophene 17 upon heating in DMF/TEA. Moreover, refluxing of compound 23 with α-haloketones afforded 3-aminothiophenes 24 and 25. Identity of newly synthesized compounds was established by the spectral data and novel compounds were evaluated as antioxidant agents.